PENGARUH KOMPENSASI, DAN LINGKUNGAN KERJA NON FISIK, TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA SEBAGAI VARIABLE MEDIASI PADA DIVISI SDM DAN ORGANISASI KANTOR PUSAT PERUSAHAAN UMUM BULOG JAKARTA - Ikhsan Rahman Wibowo (2023)
This research is a quantitative research that aims to determine the Effect of Compensation, and Non-Physical Work Environment, on Job Satisfaction Through Work Motivation as a Mediation Variable. This study used 37 employees in the HR and Organizational Division of the Head Office of the Public Company Bulog Jakarta. The data analysis technique used is PLS-based SEM. The results showed (1) compensation has a positive and significant effect on job satisfaction, (2) the non-physical work environment has a positive and significant effect on job satisfaction, (3) compensation has a positive and significant effect on job satisfaction mediated by work motivation, (4) non-physical work environment has a positive and significant effect on job satisfaction mediated by work motivation, (5) work motivation has a positive and significant effect on job satisfaction..